Unusual Case of Osteomyelitis and Discitis in a Drug User with a Background of Chronic Back Pain: Do Not Miss the Serious Etiologies - Alaa M. Ali; Moona Khan; Shawn G. Kwatra; Aram Barbaryan; Nasir Hussain; Raya Saba; Aibek E. Mirrakhimov (Case Reports in Infectious Diseases)
Chronic back pain is a common presenting complaint that is frequently encountered by clinicians. The challenge for clinicians is identifying the relatively few patients with a significant probability of a more serious problem that requires further evaluation. Such individuals require further evaluation for possible occult malignancy, infection, or fracture. We present a case of a 50-year-old male with a past medical history of chronic back pain and IV drug abuse who presented with acute back pain and in whom a diagnosis of vertebral osteomyelitis was missed during multiple visits to the emergency room.